2009
DOI: 10.1111/j.1365-3024.2009.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

The turkey, compared to the chicken, fails to mount an effective early immune response to Histomonas meleagridis in the gut

Abstract: Histomonosis is a disease of poultry caused by Histomonas meleagridis. Chickens usually recover while the mortality rate in turkeys is high. The immunological response of both species towards H. meleagridis was investigated. Parasites migrated in greater numbers to the turkey liver compared with that of chicken. Chicken mounted an effective caecal innate response, with increased expression of IL-1beta, CXCLi2 and IL-6 mRNA, resulting in control of parasite numbers. The turkey failed to mount such an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 22 publications
6
67
1
2
Order By: Relevance
“…The following cycle profile was applied: one cycle at 45°C for 10 min, one cycle at 95°C for 10 min, and 40 cycles at 95°C for 15 s and 57°C for 45 s. The results are displayed in threshold cycle values (Ct). Ct values were normalized based on the detection of 28S rRNA expression levels (Powell et al, 2009). The data are presented as fold change in mRNA expression levels in relation to ΔCt values from aMPV-free control groups (Pfaffl, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The following cycle profile was applied: one cycle at 45°C for 10 min, one cycle at 95°C for 10 min, and 40 cycles at 95°C for 15 s and 57°C for 45 s. The results are displayed in threshold cycle values (Ct). Ct values were normalized based on the detection of 28S rRNA expression levels (Powell et al, 2009). The data are presented as fold change in mRNA expression levels in relation to ΔCt values from aMPV-free control groups (Pfaffl, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…IgE production is driven by IL-5, after IL-4 induces isotype switching to IgE. In the chicken, IL-13 and IL-4 (the former up to 100-fold more than the latter) are both induced following infection with extracellular pathogens (Degen et al, 2005;Powell et al, 2009), but IL-5 expression is switched off (Powell et al, 2009). IgE is not produced in birds*chickens only have IgM, IgY (the functional equivalent of mammalian IgG), which does not have sub-types, and IgA.…”
Section: Unique Features Of the Chicken's Immune Systemmentioning
confidence: 99%
“…This may explain why the infection rates in the turkey flocks examined were indeed higher than the ones found in the broiler chicken flocks and why individual turkeys revealed higher mean culture scores than individual chickens. Powell et al found that the innate immunity in turkeys was less potent than that in chickens, resulting in a higher disease burden for Histomonas meleagridis (12). However, the higher bacterial loads in turkeys could also be explained by the occurrence of more virulent ompA genotypes and/or by the presence of mixed infections in turkeys.…”
Section: Discussionmentioning
confidence: 96%